PENGGUNAAN BAHASA GAUL WARGANET DALAM KOLOM KOMENTAR DI MEDIA SOSIAL TIKTOK - Tita Gussalina; Mustofa; Nisaul Barokati Seliro Wangi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Research on slang language on TikTok has strong relevance to contemporary linguistic studies because it reflects language development influenced by social media. This study not only identifies slang terms appearing in TikTok comment sections but also analyzes their word-formation processes and meanings. Through this research, the researcher seeks to reveal the creative processes of language use and the social meanings underlying the emergence of these slang expressions. Furthermore, this study provides an overview of the influence of social media on the development of the Indonesian language, particularly in informal communication.This research employed a descriptive qualitative method, with data consisting of comments posted by netizens on TikTok. Data were collected through library research and note-taking techniques, while data analysis was conducted using content analysis to interpret the forms and meanings of the slang expressions found in the comments.The results showed that there were 39 instances of slang language based on Muslich’s theory, including acronyms, abbreviations, contractions, clippings, and reversed forms. Acronyms were found in words such as stecu, gercep, and salfok; abbreviations in JJ, HTS, and PD; contractions in bg, dah, and bat; clippings in melow, gemoy, and bro; and reversed forms in ngab. In addition, six types of meaning were identified: lexical, grammatical, contextual, referential, denotative, and connotative meanings. The study concludes that acronym forms and denotative meanings are the most dominant types of slang used in TikTok comment sections.